PREMAN SEBAGAI PROFESI (Studi Kasus Preman Di Kelurahan Mahakeret Barat Kota Manado) - Pusung, Alfa Xaverius (HOLISTIK, Journal Of Social and Culture, 2013)
Work performed by humans although compulsion is the result of their thinking. Good and evil it does is the result of a choice by their awareness of what they are doing is taking "all the way" to get the material in the fulfillment of life. Thugs can essentially be viewed as one of the professions that exist in society. Based on this foundation, it is indistinguishable who can not be categorized goons and thugs. Thugs are people who do not want to be bound by the norms and rules that are generally accepted in the community. Those who had this same principle of life meet and terbinalah social relations among them. Finally the social pooling (social grouping). Social grouping formed by itself or accidentally is called thugs network. With the principle of life as mentioned above, the formal employment are also not promising for those who belong thugs could turn into not a thug. Oblique view of them (thugs) remains always there, although the identity of the profession is not known social environment which he occupied. This view was born out of their lives that look hard, and their edges will also be someone who is loud. Whatever they are doing good or bad, the outlook remains the same. Their views about the world of work that led to the awareness to stop what they are doing, is something separate urge within them to stop and continue to live in accordance with what is undergone by the other man. Keywords: employment, livelihood, life hard